Sustaining Quality Early Childhood Education Through Increasing Student Independence - Ida Maimunah; Akmal Mundiri; Yusuff Olatunji Abimbowo; Alma Vorfi Lama (Al-Qalam Institute, 2025)
This study focuses on the development of early childhood independence through a holistic learning approach at RA Dewi Masyitoh Kandangjati Kulon Kraksaan, Probolinggo. The purpose of this study was to evaluate the effectiveness of a holistic approach that integrates physical, social, emotional, cognitive, and moral independence, and to provide a learning model that can be widely applied in other early childhood education institutions. The research method used was a qualitative approach with a case study research type. Data were collected through direct observation, interviews with teachers and parents, and analysis of documentation related to the curriculum and child development. The data analysis technique used was thematic analysis to identify the main themes that emerged from the data that had been collected. The results of the study showed that the holistic learning approach applied at RA Dewi Masyitoh succeeded in increasing children's independence in various aspects. Children showed significant abilities in carrying out daily activities independently, interacting with peers, managing emotions, thinking critically, and understanding and applying moral values. The implications of this study emphasize the importance of a comprehensive and integrated learning approach to develop children's independence as a whole.